Pengaruh Terapi Nesting terhadap Kualitas Tidur pada Bayi Berat Lahir Rendah (BBLR) di RSUD Bendan Kota Pekalongan - Linda Mariana Beru Ginting; Menik Kustriyani; Wahyuningsih, Wahyuningsih (Journal of Medical Practice and Research, 2026)
Background: Low Birth Weight (LBW) infants are a group of neonates vulnerable to health problems due to immaturity of their organ systems, one of which is sleep quality disturbances. Suboptimal sleep quality can increase physiological stress, inhibit growth, and affect infant development. This condition is often exacerbated by the noisy and brightly lit environment of the perinatology ward or NICU. Nesting therapy is a non-pharmacological intervention that can provide comfort by mimicking the intrauterine position, but its implementation at Bendan Regional Hospital, Pekalongan City, has not been routinely and standardized. Methods: This study used a quantitative design with a pre-experimental approach. The population and sample were all LBW infants treated in the perinatology ward, using a total sampling technique according to inclusion and exclusion criteria. Data were collected using sleep quality observation sheets before and after nesting therapy, then analyzed using statistical tests. Results: The results showed an improvement in sleep quality in LBW infants after nesting therapy. Statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating that nesting therapy significantly affected the sleep quality of LBW infants. Conclusion: Nesting therapy significantly improves the sleep quality of LBW infants.